Dual Pathway Inhibition for Vascular Protection in Patients with Atherosclerotic Disease: Rationale and Review of the Evidence - Weitz, Jeffrey Ian; Angiolillo, Dominick J.; Geisler, Tobias; Heitmeier, Stefan (Thrombosis and Haemostasis, 2020)
Despite advances in secondary prevention strategies in patients with cardiovascular disease, the residual risk of recurrent atherothrombotic events remains high. Dual-antiplatelet therapy is the standard of care for secondary prevention in patients with acute coronary syndrome (ACS), whereas single antiplatelet therapy, generally with aspirin, is the standard of care for secondary prevention in stable patients with coronary artery disease (CAD), peripheral artery disease (PAD), or cerebrovascular disease. However, atherosclerotic plaque disruption not only triggers platelet activation but also results in thrombin generation because of tissue factor exposure. Therefore, blocking both pathways by combining antiplatelet therapy with an anticoagulant, or dual pathway inhibition (DPI), has the potential to be more effective than inhibiting either pathway alone. The benefit of DPI has been demonstrated in the ATLAS ACS 2-TIMI 51, COMPASS, and VOYAGER PAD trials, where the combination of rivaroxaban vascular dose (2.5 mg twice daily) plus aspirin significantly reduced the risk of atherothrombotic events compared with aspirin across a broad range of patients, including those with recent ACS, those with chronic CAD and/or PAD, and patients with PAD who have undergone peripheral revascularization. This article provides the rationale for this regimen in more detail, including why the DPI regimen with the rivaroxaban vascular dose was developed for vascular protection in a broad spectrum of patients with atherosclerotic disease.
Keywords: coronary artery disease; dual pathway inhibition; nonvitamin K antagonist oral anticoagulants; peripheral artery disease; rivaroxaban